1984
DOI: 10.1021/ma00136a011
|View full text |Cite
|
Sign up to set email alerts
|

Hindered diffusion of dextran and ficoll in microporous membranes

Abstract: The effective diffusivity of a solute within a pore of comparable size is frequently found to be less than its value in bulk solution. This phenomenon is known as "hindered" or "restricted" diffusion and it arises fundamentally from the fact that the characteristic dimension of the solute molecule is no longer small compared to that of the pore through which it passes. Hindered diffusion is observed in a number of important fields such as gel permeation chromatography, heterogeneous catalysis, and membrane sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 4 publications
(7 reference statements)
6
119
0
Order By: Relevance
“…23 Bohrer et al used light scattering techniques and suggested that ficoll was shaped more like a sphere than a rod. 24 Ohlson et al and Oliver et al reached the same conclusion. 25,26 Venturoli et al reviewed the literature and concluded that ficoll also exhibits "nonideal" properties due to an open, deformable structure and thus that it deviates from an ideally hard sphere in nature.…”
mentioning
confidence: 63%
“…23 Bohrer et al used light scattering techniques and suggested that ficoll was shaped more like a sphere than a rod. 24 Ohlson et al and Oliver et al reached the same conclusion. 25,26 Venturoli et al reviewed the literature and concluded that ficoll also exhibits "nonideal" properties due to an open, deformable structure and thus that it deviates from an ideally hard sphere in nature.…”
mentioning
confidence: 63%
“…Studies in the rat have shown that, for a given value of molecular radius, dextran passes through the glomerular capillary wall more readily than does another uncharged test macromolecule, Ficoll (6,36). Diffusion studies with synthetic membranes suggest that Ficoll behaves like the neutral, spherical molecule envisioned in the theory of hindered transport through pores, whereas transmembrane diffusion of dextran is more rapid than expected from its molecular radius (37,38). This facilitation ofdextran transport implies that the use ofdextran data to evaluate membrane pore parameters will tend to overestimate the effective pore size (36).…”
Section: Discussionmentioning
confidence: 99%
“…For artificial membranes with track-etched pores, the diffusion of dextran and Ficoll has been analyzed according to conventional hydrodynamic pore models for diffusion of hard spheres in cylindrical tubes (7). In experimental systems with such porous membranes, the agreement between data and theory was poor for dextran, whereas it was much better for Ficoll.…”
Section: In Vitro Polysaccharide Permeability Across Porous Membranesmentioning
confidence: 99%
“…In experimental systems with such porous membranes, the agreement between data and theory was poor for dextran, whereas it was much better for Ficoll. Dextran showed considerable hyperpermeability, and even when the ratio of molecular radius (a e ) to pore radius (r p ) (a e /r p ) approached unity, dextran was able to pass through the membrane (7). In other words, dextran molecules were able to pass through membrane pores with a smaller diameter than the molecule itself.…”
Section: In Vitro Polysaccharide Permeability Across Porous Membranesmentioning
confidence: 99%